2022
DOI: 10.3390/su141912734
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cross-Border Tourism in Accordance with the Principles of Sustainable Development on the Kazakhstan-Uzbekistan Border

Abstract: Kazakhstan and Uzbekistan are two leading countries of Central Asia, mutually beneficially cooperating in the field of cross-border tourism. In this study, the tourism potential of the border areas was determined on the basis of tourism infrastructure and settlement density data. The geographic coverage of the study included nine regions located within the limits of the Kazakhstan–Uzbekistan border. We proposed the application of a rating assessment of the estimated tourism resource potential of Kazakhstan–Uzb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The Tien San natural heritage site in Tashkent is located near the border of Uzbekistan and Kazakhstan. Tien San in Tashkent has been declared a natural heritage site and includes rich natural resources, as well as cultural heritage [68].…”
Section: Travel Destinations (Whs) In Uzbekistanmentioning
confidence: 99%
“…The Tien San natural heritage site in Tashkent is located near the border of Uzbekistan and Kazakhstan. Tien San in Tashkent has been declared a natural heritage site and includes rich natural resources, as well as cultural heritage [68].…”
Section: Travel Destinations (Whs) In Uzbekistanmentioning
confidence: 99%
“…Further research is needed to ensure sustainable ecosystem management and provide recommendations for facility development to preserve their value. The study found that regions with better accessibility and transport connectivity had a more diversified economy, which led to higher economic growth and development (Aliyeva et al, 2019;Sergeyeva et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Regardless of their origin, age, or degree of knowledge about regions, cross-border tourists are sensation seekers who look for unique emotions to later remember (Leick et al 2021). Although several segments of cross-border tourists (e.g., Way of St. James, rural tourism, health tourism (and thermalism), religious tourism, pilgrimage tourism) have been identified, they all have in common the interest and passion for different countries, which serves as a key motivator to visit a specific (cross-border) region (Maratovna et al 2021;Sergeyeva et al 2022;Kropinova 2021). CBR should be a product in which it is easy to establish enduring emotional relationships.…”
Section: Cross-border Region (Cbr) and Digital Communicationmentioning
confidence: 99%